Study on the release pattern of Zn in soil of ionic rare earth mining areas under different leaching conditions - Zhongqun Guo; Qiangqiang Liu; Feiyue Luo; Shaojun Xie; Tianhua Zhou (PLoS ONE, 2025)
The acidic leachate injected during the mining process of ion-type rare earth ores can damage the environmental characteristics of the soil, thereby triggering the activation and release of associated heavy metals. Severe Zn contamination has been found in the environment of ion-type rare earth mining areas, but the activation and release of Zn in the soil during the leaching process have not been fully understood. This study investigated the activation and release patterns and mechanisms of Zn in soil under different leaching agents ((NH 4 ) 2 SO 4 , MgSO 4 , Al 2 (SO 4 ) 3 ) and varying concentrations of Al 2 (SO 4 ) 3 (1%, 3%, 5%, 7%) using a simulated leaching experimental system. The results show that the activation and release patterns of Zn in the soil vary significantly under the influence of the three leaching agents. During the entire leaching cycle, the peak Zn concentration in the leachate was highest under MgSO 4 leaching, while the residual Zn content in the soil under Al 2 (SO 4 ) 3 leaching approached the high-risk environmental threshold. The high-concentration systems (5%, 7%) of Al 2 (SO 4 ) 3 significantly enhanced the activation and release efficiency of Zn in the soil compared to the low-concentration systems (1%, 3%) of Al 2 (SO 4 ) 3 . (NH 4 ) 2 SO 4 mainly promotes the activation and release of Zn through ion exchange between NH 4 + and Zn 2+ and the acidification effect; Al 2 (SO 4 ) 3 , on the other hand, dominates the activation and release of Zn by providing a strongly acidic environment and dissolving and damaging the mineral lattice; while MgSO 4 not only exchanges ions between Mg 2+ and Zn 2+ , but also alters the soil colloidal structure, facilitating Zn activation and release. The promoting effects of the three leaching agents on the transformation of Zn in soil follow the order of Al 2 (SO 4 ) 3 > (NH 4 ) 2 SO 4 > MgSO 4 , with the environmental risk assessment index (RAC) being highest after Al 2 (SO 4 ) 3 leaching, indicating the greatest potential environmental risk. Compared to the other three concentrations (1%, 5%, 7%) of Al₂(SO 4 ) 3 , the 3% concentration of Al 2 (SO 4 ) 3 had the most significant promoting effect on the transformation of Zn in soil. This study provides a theoretical basis for optimizing the green mining process of ion-type rare earth ores and preventing heavy metal pollution, and offers scientific support for revealing pollution mechanisms and formulating remediation and risk assessment strategies.